Designing and explaining the improvement model of women's employability capacity with emphasis on the 7th development plan - Mahsa Vahidpour; Akbar Etebarian Khorasgani; Mehrban Hadi Peykani; Saeed Daei-Karimzadeh (ارزش آفرینی در مدیریت کسب و کار)
AbstractThe aim of the current research is to design a model for the development of women's employability capacity with an emphasis on the seventh development plan. This qualitative research was compiled using thematic analysis; in this research, using semi-structured interviews with 23 experts in the field of policy making, entrepreneurship and management, the findings were combined and the present model was designed. Based on this, by analyzing the content of the interviews using the Maxqda 2020software, the relevant dimensions and codes were extracted and the importance and priority of each was determined using Shannon's entropy technique. Based on the research approach, 34 concepts and 109 codes were extracted. Supportive policies, territorial development, skill capacities, entrepreneurship platform, explanation of women's employment document and educational system gained the highest importance coefficient. In this research, the development model of women's employability capacity was presented with an emphasis on the 7th development plan. Since a comprehensive model for women's employability with emphasis on the 7th Development Plan has not been presented so far, this research can be useful in promoting women's employment, social development, and job equality.Extended Abstract                                           IntroductionEmployability is a measure that shows how desirable a person is among the workforce based on his skills and knowledge (van Harten et al, 2022). Employability skills are important because they make easier the people's recruitment for employers and increase their chances of getting and keeping a job (Chang, 2016; Abelha et al, 2020). According to the vision document of 2025, obtaining qualified and expert human resources is necessary to improve the country's position in the global economy. One of the most important criteria for measuring the degree of development of a country is the importance and prestige that women have in that country. The human development index for women in developed countries is 80%, in underdeveloped countries it is 60% for men, and in Iran, the index is 61% for men. Examining the causes of this difference in underdeveloped countries shows that in developed countries, most of this difference is caused by the level of employment and wages, while in underdeveloped countries, in addition to the differences related to the labor market, differences in education, health and Nutrition is also observed (Najirad et al, 2003). The general policies of the 7th Development Plan are priority of economic progress combined with justice. The goal of the 7th development plan in Iran is to achieve a fair economic progress with an average growth rate of 8% during the duration of the plan. The challenge of investigating the development of women's employment capacity with emphasis on the seventh development plan lies in the existing gender inequalities in the workforce. Women often face barriers to employment and career advancement, including limited access to education and training, discriminatory hiring practices, and unequal payment. The problem is that these barriers lead to underrepresentation of women in some industries and leadership positions, causing a loss of talent and potential economic growth.The current research will be done with the aim of designing and explaining the development model of women's employability capacity with emphasis on the seventh development plan; a research that covers the existing research gap and will be useful in the development of literature in the research field. The main question of the research is raised as follows: What is the development pattern of women's employability capacity with emphasis on the 7th development plan?Research literatureEmployability is the ability of people to get a suitable job. The measurement of employability should be done by considering all dimensions (Delva et al, 2021). Lee argues that despite the existing notions, employability is not defined in terms of skills, rather learning plays an important role in this process and creates constructive experiences, so employability is defined as a learning process. Continuous learning continues even after employment. With this statement, Harvey aims to differentiate employability and how to measure it. Other definitions of employability are: 1. The ability to obtain primary employment; hence the interest in ensuring that 'key competences', career advice and understanding about the world of work are embedded in the education system. 2. The ability to maintain employment and "transition" between jobs and roles within the same organization to meet new job requirements. 3. The ability to obtain a new job if necessary, that is, to be independent in the labor market with the desire and ability to manage one's job transfer between and within work organizations using optimal effort. 4. A person's capacity to continuously develop and improve their skills to maintain relevance and attractiveness in the labor market (Gürbüz et al, 2022). Based on business strategies in sharing economies, learning job techniques and acquiring qualifications have a significant impact on the employability process. McQuaid and Lindsay (2005) have introduced two alternative views in the discussions related to employability. The first point of view is expressed based on the individual's personal abilities and talents. Another point of view considers the external factors of labor market organizations, economic and social conditions; and states that these factors may affect the probability of a person's success in getting a job and promoting his career. Employability is highly dependent on the analysis of job elements and describes people's attitude and perception of jobs and peers. Therefore, employability is the opportunity to obtain and maintain a job (Reilly et al, 2016).Research methodologyThe current research is based on qualitative research in the inductive paradigm and is applicable in terms of purpose. The statistical population of this research was experts and professors in the field of policy making, entrepreneurship and management; according to the purpose of the research, sampling was done in a purposeful way using the snowball technique and with the number of 23 people. The sample size was determined using the principle of theoretical saturation in such a way that no new factor was identified after interviewing the 21st and 22nd people, and the interview process ended with the 23rd person. The interviews were conducted face-to-face with open questions, and then, using the coding process, the components of the women's employability capacity development model were identified with an emphasis on the seventh program. Based on this, by analyzing the content of the interviews using the 2020 Maxqda software, the relevant dimensions and codes were extracted and the importance and priority of each was determined using Shannon's entropy technique. Research findingsAccording to the analysis of the interviews, the categories were written in the form of references. Based on the analyzes conducted with the help of the theme analysis method, a total of 34 concepts and 109 codes were discovered and labeled for the components of the development of women's employability capacity with emphasis on the seventh program in this research. Based on this, the policy makers and those in charge of employment in the country should acquire recognition and detailed knowledge of the components of the development model of women's employability capacity with emphasis on the 7th development plan, such as support policies, challenges related to gender discrimination, territorial development, need assessment, value chain analysis, strategic alignment, dealing with island thinking, talent management, skill capacities, strategic balance, entrepreneurial platform, governing management structure, formation of think chambers, explanation of women's employment document, cognitive complexity, synergy, policymakers' attitude, knowledge sharing culture, empowerment, integration mechanisms, focus on core issues, community employability culture, networking, honoring the status of women, professionalization, decentralization, job-employee fit, cultural enrichment, information platforms, educational system, financial support, cognitive flexibility, control and supervision system and economic infrastructure. Supportive policies, territorial development, skill capacities, entrepreneurship platform, explanation of women's employment document and educational system gained the highest importance coefficient.ConclusionThe seventh program is the development of the fourth paragraph of Iran's 20-year vision document; it is the first program in line with the realization of the declaration of the second step of the Islamic Revolution, and the first program that, for the realization of justice in the area of ​​the land, has made the approved documents the basis of an integrated approach to the land, and paid serious attention to and focus on the key issues with a problem-oriented approach; and in this program, the government's priority programs are clear and can be cited in the program due to the existence of the People's Government Transformation Document. The axes of public culture enhancement in consolidating Iranian Islamic lifestyle, national identity promotion, national solidarity and trust, women's growth and prosperity, family institution consolidation, social health promotion and social damage prevention are emphasized in this program in order to be properly introduced into macro policies. In this program, emphasizing the need to create platforms for women's employability, the undeniable role of women in the development of knowledge-based economy and job creation has been emphasized. Therefore, the existence of a model in order to improve the employability capacity of women can reveal various aspects of this matter and be an important step in achieving the planned goals. The findings of the research, such as communication skills and technical skills as the codes of the category of skill capacities, are in line with the research results of Movahedi et al (2019). Also, the educational system is consistent with the research results of Ricci et al (2021), Hassan et al (2020), Wu (2019), Faulkner et al (2019). The research findings in the field of information platforms are consistent with the research results of Hassan et al (2020), Pappas et al (2018) and Movahedi et al (2019). The findings of the research in the field of the ruling management structure are consistent and compatible with the research results of Movahedi et al (2019). The development of employability capacity should be done at the local level first and according to geographical needs. It is suggested that the coordination deputy of economic affairs of the governorates conducts a detailed analysis of the local conditions and uses the capacities of the employment trustees of the provinces, such as agricultural jihad, industrial towns, industry and mining organization, and banks. Obviously, due to the requirement of economic institutions to respond to this deputy at the provincial level, the approvals of this deputy are mandatory. The Supreme Council of Employment, as the official authority for dealing with employment challenges, should place the issue of women's employability among its work priorities.